Era Disrupsi Digital pada Perkembangan Teknologi di Indonesia - Erick Saragih; Vip Paramarta; Grace Imelda Thungari; Beauty Kalangi; Kezia Marcelina Putri (Universitas 17 Agustus 1945 Semarang, 2023)
The Digital Era is a time where information can be accessed and disseminated very easily using digital technology. Globally, technology is present to help humans carry out various activities. So the era of technological disruption is something that needs to be faced. In order to continue to be able to provide the best for individuals and community groups in the business world, it is necessary to carry out various innovations and improve the quality of skills. The aim of this literature research is to find out how the era of digital disruption has affected technological development in Indonesia. The research method used is descriptive theoretical study, namely a method that discusses several possibilities for solving actual problems by collecting data, compiling or classifying them, analyzing and interpreting them with existing theories and comparing them from literature sources. The research results show that the era of digital disruption in Indonesia has developed and has entered the modern era, such as digital technology disruption in the fields of health, finance and education. It can be concluded that digital disruption is an innovation that changes people's way of life and thinking patterns, changes company work culture, or even creates new markets that have never existed before. So it has positive and negative impacts with the era of digital disruption. Therefore, if it is not faced with the right strategy, technological disruption can threaten conventional businesses and threaten industrial markets. In facing technological/digital disruption, companies need to improve the quality of more modern technology so that they are not left behind and can compete with industry and companies as well as improving the quality of human resources.